Current Challenges in Understanding the Cellular and Molecular Mechanisms in Niemann–Pick Disease Type C1 - Bräuer, Anja U. (Int J Mol Sci, 2019)
Rare diseases are a heterogeneous group of very different clinical syndromes. Their most common causes are defects in the hereditary material, and they can therefore be passed on to descendants. Rare diseases become manifest in almost all organs and often have a systemic expressivity, i.e., they affect several organs simultaneously. An effective causal therapy is often not available and can only be developed when the underlying causes of the disease are understood. In this review, we focus on Niemann–Pick disease type C1 (NPC1), which is a rare lipid-storage disorder. Lipids, in particular phospholipids, are a major component of the cell membrane and play important roles in cellular functions, such as extracellular receptor signaling, intracellular second messengers and cellular pressure regulation. An excessive storage of fats, as seen in NPC1, can cause permanent damage to cells and tissues in the brain and peripheral nervous system, but also in other parts of the body. Here, we summarize the impact of NPC1 pathology on several organ systems, as revealed in experimental animal models and humans, and give an overview of current available treatment options.